Mídia podcast na Ciência da Informação: informações situacionais apresentadas em conteúdos sobre o novo coronavírus (COVID-19). - Silva Júnior, Carlos Lima da (Brasil, 2021)
Situational information is shared in crisis situations in the world, whether from the social or physical environment, it is information that can help people in critical moments, for example in the pandemic caused by the new coronavirus (COVID-19) which can influence decision-making in the people in relation to the virus. The information is disseminated through several communication channels, but the present research emphasizes the podcast media, which gained considerable visibility in the period 2019-2021. Therefore, the research aims to analyze whether there are competence indicators that add value to situational information disseminated in CI podcasts on COVID-19. The methodology was divided into three parts: (i) identification of podcasts in Library and Information Science; (ii) classification of information in podcast episodes; (iii) identification of elements and aspects that influence the situational information in podcasts. With that, the research is of an applied character, whose objectives are descriptive and exploratory, the qualitative approach and the procedures, a bibliographical part and a field part. In the results it is possible to observe that there are 18 CI podcasts, but only 9 are active, they are; In addition to the Shelves, Biblioquê?, Librarian, Simplify, Let me tell you, Farol-Conexões, Foca na Info, Museológica Podcast and Plurissaberes. The situational information disseminated by Ci's podcasts was about how information units are dealing with the pandemic, what were their methods to continue their services, the role of information professionals in combating COVID-19, how information units can helping people without access to information at the time of the pandemic, emotional support and how to seek help with fun information to distract yourself and with guest mental health experts, inquiries into local government decision-making, combating rumors about COVID-19.